The difficulty of living well: effort and failure in the good life - Moore, Jesse Alexander (Rhodes University, Faculty of Humanities, Department of Philosophy, 2008)
We all want to live good lives, but due to the difficulty involved, few of us ever succeed. We usually either fail in our attempts to live well or remain with our safer, and less worthwhile, options. In spite of this, there has been little, if any, investigation of the role that difficulty plays in our attempts to live well, and thus in our conceptions of the good life. Within the field of the good life, philosophers tend to acknowledge the fact that good lives are difficult to live, and leave it at that. Since we must all face the difficulty of living well, the lack of analysis of the implications of difficulty seems a glaring oversight. In order to redress this, I explore the role that difficulty plays in two requirements for living well, namely achievement and reflection. Firstly, I examine the relationship between effort and achievement. I argue that difficulty just is the requirement of effort, and that it is required in order for our achievements to be meaningful and for us to value them. Secondly, I look at the relationship between failure and reflection. I argue that reflection on our failures can lead us to knowledge that helps us to live well and that we would not usually come to if we did not fail. Finally, I look at the roles of effort and failure in some accounts of the good life and I draw on psychological research and theory to provide support for my conclusions about the positive effects of effort. I conclude by examining the implications of reducing difficulty for the future of humankind.
Keywords: Conduct of life; Ethics; Happiness; Values; Failure (Psychology); Success; Struggle